Peningkatan Efisiensi Penanganan Material Melalui Perancangan Tata Letak Fasilitas dengan Integrasi Metode Konvensional Tata Letak dan Algoritma CORELAP - Rachman, Taufiqur (Metris: Jurnal Sains dan Teknologi, 2021)
Material handling methods determine the effectiveness and efficiency of a company. This research was conducted at PT. FIM which is a manufacturing company that produces food packaging made of plastic (plastic food grade packaging), which has ineffective and inefficient material handling problems. The main objective of this research is to design the facilities layout of PT.FIM to improve the efficiency of material handling. In this research, the integration of the conventional layout method and the CORELAP algorithm was used to determine the optimal work station layout. The research stage begins with calculation of the routing sheet based on the OPC, calculation of the floor area and making of ARC in the production area using the CORELAP algorithm method, while for other facility areas using the conventional layout method. The next stage is making ARD and AAD, and conducting MHPS analysis. From the results of this research obtained a layout design that requires the addition of 6 injection machines, a production floor area of 922m2, a raw material warehouse of 26.65m2, a finished materials warehouse of 63.96m2, a work-in-process warehouse of 85.28m2, supporting materials warehouse of 14.34m2, office area and other facilities area of 462m2. The resulting layout design has a material handling distance difference of 49.3m, and a cost difference of Rp.51,978, with a material handling cost efficiency of 78.67%.